Effect of Crushed Concrete on Some Properties of Modified Reactive Powder Concrete Reinforced With Micro Steel Fibers - Rusul Hussain Saeed; Nada Mahdi Fawzi (Journal of Engineering)
Conventional RPC does not contain coarse content aggregate, but some researchers incorporate coarse aggregate. Those researchers used coarse aggregate to produce RPC, the new RPC known as modified reactive powder concrete (MRPC). This paper shows the findings of a study that looked into using crushed concrete as aggregates. The crushed concrete was taken from examined cube spacemen of a road project in the city of Baghdad and then crushed until they were no bigger than 10 mm. Micro steel fibres (1% by volume of the concrete) and crushed concrete (25% and 100%) of the original reactive powder concrete were added to the mix instead of fine sand and micro steel fibres before the casting. Look into several properties of the standard and reactive powder concrete, including their density, compressive Strength and flexural Strength. Compressive Strength of modified reactive powder concrete with 25% crushed concrete  increased by 16.86% and 10.57 and  slightly increasing  by 4.81% Moreover, 3.84% at age 7 days and   28 days of testing, respectively, when 100% crushed concrete was used instead of sand when compared with the reference mixture. When 25% crushed concrete was incorporated, Flexural Strength increased by 44.33% and 29.85 and when 100% crushed concrete was incorporated, Flexural Strength decreased by 14.15% and 12.68%% at age 7 days and 28 days, respectively, when compared with the reference mixture